2018
DOI: 10.5465/amj.2015.1325
|View full text |Cite
|
Sign up to set email alerts
|

When the Dust Settles: The Consequences of Scandals for Organizational Competition

Abstract: International audienceRecent works have documented the dark side of scandals, revealing how they spread, contaminate associated organizations, and taint the perception of entire fields. We complement this line of work by exploring how scandals durably affect competition within a field, translating into relative advantages for certain organizations over others. First, scandals may benefit organizations that provide a close substitute to the offerings of the implicated organization. Second, scandals pave the way… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
73
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(74 citation statements)
references
References 73 publications
1
73
0
Order By: Relevance
“…We are aware of only one study where the valence of the spillover is different than the valence of the action-that is, where a negative action has a positive spillover effect on others. Piazza and Jourdan (2018) found that when the Catholic Church became embroiled in sex scandals in the United States, other Christian denominations that were perceived as having stricter standards of conduct were able to increase their membership at the Catholic Church's expense. While they explored this effect over a long time period, the "pedophile priest" sex scandals continued to be in the news during the entire period of their study, keeping the Catholic Church's wrongdoing cognitively available (Fiske & Taylor, 1991;Tversky & Kahneman, 1973) in the minds of parishioners, and thus a continued focus of their attention.…”
Section: Introductionmentioning
confidence: 99%
“…We are aware of only one study where the valence of the spillover is different than the valence of the action-that is, where a negative action has a positive spillover effect on others. Piazza and Jourdan (2018) found that when the Catholic Church became embroiled in sex scandals in the United States, other Christian denominations that were perceived as having stricter standards of conduct were able to increase their membership at the Catholic Church's expense. While they explored this effect over a long time period, the "pedophile priest" sex scandals continued to be in the news during the entire period of their study, keeping the Catholic Church's wrongdoing cognitively available (Fiske & Taylor, 1991;Tversky & Kahneman, 1973) in the minds of parishioners, and thus a continued focus of their attention.…”
Section: Introductionmentioning
confidence: 99%
“…Even if only one individual or one organization is objectively involved in a scandal, it is common to suspect that more people and/or organizations have been misbehaving, that is, behaving in a scandalous way. For instance, reactions to corporate deviance, such as customer loss and stock‐value loss, have been found to spill over into organizations unrelated to an identified culprit but that nonetheless share similar characteristics with it (Jonsson et al 2009; Piazza and Jourdan 2018). Thus, after the Volkswagen diesel scandal was uncovered, great concerns arose about the behavior of other car manufacturers, which very rapidly came under suspicion of having behaved in the same way as Volkswagen.…”
Section: A Strategy To Disadvantage Rivals or Foesmentioning
confidence: 99%
“…With the rise of social media, this form of media competes with traditional media in shaping information flows and discourses during a scandal. Any social media user, including celebrities, journalists, politicians, academics and, more generally, any citizen willing to comment is given a voice in the debate (Piazza & Jourdan, 2018). Social media has a global reach as was illustrated by scandals such as the “Me Too” movement.…”
Section: Influencer Marketing and The Risks Around Scandalsmentioning
confidence: 99%
“…Social media has a global reach as was illustrated by scandals such as the “Me Too” movement. A major scandal may now become a worldwide event in a matter of hours, as information about the accused firm, its rivals, and the entire industry disseminates across the globe way beyond the parameters of the local or national communities in which scandals used to be confined (Piazza & Jourdan, 2018).…”
Section: Influencer Marketing and The Risks Around Scandalsmentioning
confidence: 99%